The Brain And The Bat: A Popular Criminology Of The Brain In The Batman Animated Universes. Issue 5 (4th May 2022) - Kort-Butler, Lisa
ABSTRACT: Technology has made the brain both accessible and visible to researchers and the public at large. The threads connecting the neuroscience of criminality and its representations in popular culture are detectable in a variety of locations, including the Batman animated series, which historically parallel the expansion of neuroscientific technologies. Framed by insights from popular criminology and gothic criminology, this project traced how representations of crime in popular culture intersect with representations of the brain, analyzing how the brain is positioned as an explanation for deviance and criminality. In the series, the brain was vulnerable to external forces, causing characters' deviance. The brain was also a source of power, a trait that was inherently criminal. Characters deemed capable, but who failed to control themselves, were culpable for their criminality, regardless of their "abnormal" brains. Such representations of dysfunctional and technologically-altered brains speak to the complementary nature of popular and scholarly approaches to deviance.